Quantitative Analysis of Calcium Phosphate Nanocluster Growth Using Time-of-Flight Medium-Energy-Ion-Scattering Spectroscopy - Park, Jimin; Yang, Ki Dong; Kim, Na-Young; Jung, Kang-Won; Le, Viet-Duc; Lim, Hee-Jin; An, Junghyun; Jin, Kyoungsuk; Kim, Yong-Hyun; Nam, Ki Tae; Moon, DaeWon (AMER CHEMICAL SOC, 2018)
One of the remaining challenges in material chemistry is to unveil the quantitative compositional/structural information and thermodynamic nature of inorganic materials especially in the initial nucleation and growth step. In this report, we adopted newly developed time-of-flight medium-energy-ion-scattering (TOF-MEIS) spectroscopy to address this challenge and explored heterogeneously grown nanometer-sized calcium phosphate as a model system. With TOF-MEIS, we discovered the existence of calcium-rich nanoclusters (Ca/P similar to 3) in the presence of the non-collagenous-protein-mimicking passivating ligands. Over the reaction, these clusters progressively changed their compositional ratio toward that of a bulk phase (Ca/P similar to 1.67) with a concurrent increase in their size to similar to 2 nm. First-principles studies suggested that the calcium-rich nanoclusters can be stabilized through specific interactions between the ligands and clusters, emphasizing the important role of template on guiding the chemical and thermodynamic nature of inorganic materials at the nanoscale.